PERAN PENTING PERSONEL SEKOLAH DALAM MENDUKUNG KEBERHASILAN PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH - Feni Listari; Neviyarni; Firman (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
Schools are educational institutions where students study and provide services that have a good management system. It is impossible for a guidance and counseling service program to be implemented well if it is not supported by school personnel, the following are school personnel related to guidance and counseling service activities including: principal, deputy principal, guidance teacher coordinator (counselor), guidance teacher and counseling, administrative staff, subject teachers and homeroom teachers. Relationships with the duties of each school personnel are certainly very helpful in the success of guidance and counseling programs in schools. So here it is very necessary for organizational management and administration of guidance and counseling in schools to create good performance among school personnel in supporting the success of the guidance and counseling program in schools. Organization and administration of guidance and counseling as an effort to manage and mobilize various personnel and materials in order to achieve the objectives of guidance and counseling. So that the work of guidance and counseling services runs smoothly, efficiently and effective